Controlul administrativ – garant al legalităţii actelor administrative - Cebotarescu, Cătălina (CEP USM, 2024)
In order to shape a modern and democratic society, it is absolutely necessary that the transformations in society take place in a well-determined sequence and with adequate legislative support, which would allow and guarantee not only an efficient administration of state affairs, but also that the authorities to the state to reform themselves, in close accordance with the requirements formulated and advanced by the evolution of society. The administrative control is a guarantee of compliance with the principle of legality in all manifestations of the public administration, through it possible deviations from the legal norms can be discovered and concrete measures for correction and, possibly, optimization of the law enforcement action can be established.